(3TQM cdjGJ GdbGfhf dGHf SjfGs - (3bWH GdOjf eMehO Hf eSYhO Hf eUWdM GdTjQGRis; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3bGd GdTjN QMeg Gddg (B: (3GdLedI GdKGfjI ef GdJYdje GdKGdK ef Gdaf GdKGfi ai GdHhd hGdHQGR ,hgj KdGKI YTQ aUdG(B: (3GdaUd GdChd ,bhd cdi ai GdHhd , hgPG GdaUd jTJed Ydi eHGMK s
(3BNQgG (B:s
(3eHJhQ ,hBNQ GdehLhO efgG hEf ddUaQGA cGdeQCI GdSdjWI , agi HDPi HWhd dSGfgG ,EdG Cf QLhYgG SQjY hHdG MbO hGdHdZe eKdg ceKd Gdedc GdPi CONd Ydjc ajLH Cf JJdWa ai CeQg s
(3fSNI KGdKIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B134 s
Keywords: (3GdWHs